Using 3D-printing for education on of foundry students - Kononchuk, S.; Skrypnyk, O.; Pukalov, V.; Конончук, С. В.; Скрипник, О. В.; Пукалов, В. В. (Wloclawek: Republic of Poland, 2019)
The study of additive technologies gives foundry students a better understanding of the casting design, casting system, features of placement and mounting of the rod in the form, design, sequence of manufacture and location on the plates of modeling equipment, design and operation of mechanisms, and obtaining competencies in particular, the ability to think and reproduce spatial objects, structures and mechanisms in the form of projection drawings and three-dimensional geometric models, to use computer-aided design (CAD), manufacturing (CAM), engineering research (CAE) and specialized application software to solve engineering problems.
Використання 3D-друку для навчання студентів-ливарників
Keywords: 3D-printing; 3D-model; education; student; competencies; additive technologies; computer design; 3D-друк; 3D-модель; освіта; студент; компетентності; адитивні технології; комп’ютерне проектування